PERBANDINGAN PEMBERITAAN DAHLAN ISKAN TERKAIT KASUS TERSANGKA DUGAAN KORUPSI GARDU INDUK DI SURAT KABAR RIAU POS DAN TRIBUN PEKANBARU - Mayasari, Tri; ", Suyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Status of the suspects dropped Jakarta Provincial Prosecutor to Dahlan Iskan in cases of suspected corruption substation on June 5, 2015. As two major newspapers that compete in Riau, Riau Pos and Tribun Pekanbaru certainly not miss to made this a national issue as a material news. Differences in background made Riau Pos and Tribun Pekanbaru tried to presented the information to the packaging of different discourse to the public in accordance with the vision and mission adopted. Therefore, this study aims to determine how the macro-structure comparison, superstructure, and microstructure news Dahlan alleged corruption cases related to the substation of Riau Pos and Tribun Pekanbaru This study used a qualitative approach to discourse analysis models Teun A Van Dijk. Data was collected by interview and documentation. The object of ten research news, consists of five news from Riau Pos and five news from Tribun Pekanbaru. Informants consisted of two people who are the newspaper editors by using purposive technique. To achieve the validity of the data in this research, researchers used triangulation. The results showed: first, the macro level Riau Pos news related to this case is the theme of the trip compared Tribun Pekanbaru legal cases that focus highlights the personal realm of Dahlan Iskan. Second, the level of the superstructure showed that Riau Pos trying to establish a pattern of reporting the case that the determination of Dahlan as a suspect by the Prosecutor not through legal channels in accordance with the Criminal Procedure Code Tribune Pekanbaru different from that formed schema that figure Dahlan is the figure of a brave and responsible to face the case. Thirdly, the micro level showed that Riau Pos shows the tendency preaching through background polemics reveal detailed legal case through news stories than the Tribune Pekanbaru better preserve the independence proclamation by taking background information from the parties that is quite neutral in dealing with this case.Keywords : News Comparison, Dahlan Iskan , Substation, Alleged Suspect, CorruptionCase